Conhecimentos de crianças sobre o sistema de numeração: o desafio de utilizar eficazmente a numeração escrita - Monteiro, Maria Priscila Bacellar (2016)
The present study is built on the results that showed that the mistakes children make solving operations using the conventional technique are due to the lack of comprehension of the rules of the numeral system we use nowadays. The researches also indicated that premature introduction of denominations of “ones”, “tens”, “hundreds”; conventional technique; and the use of objects to materialize base-10 don’t necessarily lead to the comprehension of rules and often keep the children from making meaning of mathematic knowledge. This study aims to analyze the strength of a didactic sequence elaborated by Lerner and her staff and focused on the teaching of the positional numeral system. The proposed activities involved the anticipation of calculation results and the elaboration of valid rules that would lead to the understanding of decimal grouping. The research was conducted in three classes of second grade of elementary school of a public school in São Paulo. Participated 91 students between seven and eight years and three teachers of their classes. The activities were previously discussed with the teachers; they were responsible for conducting classes and observed by the researcher. The developed sequence proved to be powerful for the advancement of the children in the understanding of what is hidden in the numeral system we use and indicated that a rupture on the current didactical contract is necessary so that they take responsibility for solving the proposed problems and advance in their conceptualizations